1997
DOI: 10.1136/jcp.50.11.923
|View full text |Cite
|
Sign up to set email alerts
|

Determination of proliferative activity in nasal polyps.

Abstract: Aims-To determine the level ofproliferative activity in 39 nasal polyps with clear cut distinct clinical behaviour patterns. Methods-The 39 nasal polyps included 11 polyps labelled as "single" and taken from the lateral nasal wall and the middle turbinate; 12 polyps labelled as "massive" and relating to diffuse polyposis involving the entire nasal cavity; six polyps labelled as "ASA" and relating to nasal polyps from patients with acetylsalicylic acid intolerance and asthma; and 10 polyps from cystic fibrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…We conclude from this observation that LSC analysis of FNABs can be applied for the determination of the ploidy of a tumor pre-operatively. In our opinion LSC might have some advantages as compared to image cytometry: (A) with LSC much higher cell counts can easily be achieved than with image cytometry (about 300 cells for routine examinations) [18,31,39,40]; however, this increase in cell count very likely will not result in different ploidy values but rather in the detection of rare cells such as mitotic cells [12]. (B) In image cytometry cells are selected by the observer and therefore a substantial bias on the malignant cell population might result from preferring grossly atypical cells; this needs training in morphological analysis and helps to concentrate on the most interest-ing cells (i.e., the malignant cells) but could explain the sub-optimal correlation of the 5cER determined by image cytometry and LSC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude from this observation that LSC analysis of FNABs can be applied for the determination of the ploidy of a tumor pre-operatively. In our opinion LSC might have some advantages as compared to image cytometry: (A) with LSC much higher cell counts can easily be achieved than with image cytometry (about 300 cells for routine examinations) [18,31,39,40]; however, this increase in cell count very likely will not result in different ploidy values but rather in the detection of rare cells such as mitotic cells [12]. (B) In image cytometry cells are selected by the observer and therefore a substantial bias on the malignant cell population might result from preferring grossly atypical cells; this needs training in morphological analysis and helps to concentrate on the most interest-ing cells (i.e., the malignant cells) but could explain the sub-optimal correlation of the 5cER determined by image cytometry and LSC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferative studies are reported for nasal polyps (65), and nasal inverted papillomas (66) and interestingly Kotelnikov et al (67) described the labeling index (LI)-as evaluated by bromodeoxyuridine-in nasal non-neoplasic pseudostratified epithelium in patients with head and neck tumors. The LI in four samples was 11.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In murine models this has been proposed to be due to increased cellular proliferation and/or reduced apoptosis [17,18]. In human studies increased cellular proliferation has been demonstrated in the airways and in nasal polyps in patients with CF compared with non-CF subjects [19][20][21]. Increased cellular turnover in the CF gut may be linked to an increased incidence of gastrointestinal malignancy [5,6], which becomes more relevant as the median age of survival in CF extends well into adulthood [22].…”
Section: Introductionmentioning
confidence: 99%